Anmeldelser - Trærup, Birthe (Danish Yearbook of Musicology, 1993)
Review of: Vagn Holmboe: Danish Street Cries. A study of their musical structure and a complete edition of tunes with words collected before 1960. Forlaget Kragen ApS. København 1988. (Acta Ethnomusicologica Danica 5, Dansk Folkemindesamling Skrifter 6).